2007
DOI: 10.1186/1471-2482-7-15
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of intraoperative methylene blue enemas to assess the integrity of a colonic anastomosis

Abstract: BackgroundIntraoperative testing of colonic anastomoses is routine in assuring anastamotic integrity. We sought to determine the efficacy of the methylene blue enema (MBE) as an intraoperative test for anastomotic leaks.MethodsThis study is a retrospective review of consecutive colonic operations performed from January 2001 to December 2004 in a community hospital setting by a general surgical group that uses the MBE exclusively. All operations featuring a colonic anastomosis and an intraoperative MBE were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 8 publications
(8 reference statements)
0
38
0
Order By: Relevance
“…The thirteen reviewed studies included a total of N=3,023 patients (Table 3), [16,17,[19][20][21][22][23][24][25][26][27][28][29]. Study sample size and design was variable.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The thirteen reviewed studies included a total of N=3,023 patients (Table 3), [16,17,[19][20][21][22][23][24][25][26][27][28][29]. Study sample size and design was variable.…”
Section: Resultsmentioning
confidence: 99%
“…Suture repair (74.7%) was the most common method of anastomosis correction used followed by takedown and re-anastomosis (17.3%) and diversion (8.0%). No significant differences in intraoperative leak rates were found were found across anastomosis types (staple: 4.9%, suture: 2.3%, and compression: 0.0%, p=0.066) in the 10 studies that reported leak based on type of anastomosis employed [16,[19][20][21][22][24][25][26][27][28]. Six articles reported on the rate of intraoperative leaks by surgical technique used (laparoscopic v. open) [22,[25][26][27][28][29].…”
Section: Search Term Description Definitionmentioning
confidence: 99%
See 3 more Smart Citations